Investigating the improvement of nursing students’ clinical competence through the mastery learning approach compared to the traditional method in the oncology department: A mixed-methods study - Mohsen Masoumian Hosseini; Fateme Ruhabadi; Azam Gazerani; Seyedeh Toktam Masoumian Hosseini; Hosnieh Raoufian; Vahid Moeini; Akram Gazerani (Journal of Medical Education Development, 2023)
Background & Objective: Providing exceptional attention to cancer patients requires nursing education in the oncology unit. Thus, this study aimed to acquire and improve clinical competency in nursing students through the Mastery Learning approach and compare it with traditional education. Materials & Methods: This study used a mixed-method (exploratory sequential design) approach to develop a clinical competency checklist and evaluate students' skills through Mastery Learning. This research started with a qualitative study and continued with a quantitative one. We developed the checklist using a three-round Delphi method, comprising 41 items based on 7 criteria. An internship program was offered to 20 nursing students in two groups (i.e., Mastery Learning training and traditional training) at the oncology department of Hakim Hospital, Neyshabur, Iran, for one semester. To assess the impact of the intervention on students' anxiety, an Evaluation Apprehension Measure questionnaire was administered to each student before the posttest, followed by a 5-item objective structured clinical examination (OSCE) to assess students' final skills. The competency and anxiety questionnaire was also checked for reliability and validity. Results: For the clinical competence checklist, 41 out of 52 items showed more than 80% agreement. The results of the anxiety test demonstrated that students receiving Mastery Learning were moderately anxious, while students undergoing traditional training had high levels of anxiety. The results of the OSCE test showed that the students in the Mastery Learning group had significantly higher scores than their peers in the traditional training group. Conclusion: This study found that Mastery Learning led to a reduction in test anxiety and an increase in clinical competence.